This Time is Different? Higher Education and AI’s Impact on the Labor Market - Teixeira, Pedro (International Higher Education, 2025)
The last two centuries’ historical experience has shown that technology has consistently replaced human labor in specific tasks without leading to widespread job loss, reinforcing instead the labor market advantages of higher education. Despite that optimism, growing concerns have permeated policy views about digitalization and its impacts on the labor market. This text examines briefly those concerns and some potential implications for higher education, with a particular emphasis on the role of educational mission, pedagogical and curricular innovation, and the institutional conditions favorable to face those challenges.